Competitive strategy : techniques for analyzing industries and competitors : with a new introduction - Porter, Michael E., 1947- (Free Press, 1998)
"Now nearing its 60th printing in English and translated into nineteen languages, Michael E. Porter's Competitive Strategy has transformed the theory, practice, and teaching of business strategy throughout the world. Porter introduces his three generic strategies - lowest cost, differentiation, and focuswhich bring structure to the task of strategic positioning. He shows how competitive advantage can be defined in terms of relative cost and relative prices, thus linking it directly to profitability, and presents a whole new perspective on how profit is created and divided." "The ideas in the book address the underlying fundamentals of competition in a way that is independent of the specifics of the ways companies go about competing."--BOOK JACKET.